إدارة الجودة الشاملة في حجرة الدراسةحل المشكلات أداةً - زيان شامي (مجلة الآداب و العلوم الإجتماعية, 2014)
Talking about total quality in general is not easy; discuss total quality in education is a challenge, explore ways to improve performance in the areas of education is not a luxury we can happen, however, to do so, you must know as well the peculiarities of this area as total quality, and trying to find a suitable approach to solving the problem.